The Equivalence of Cultural Terms in the Keonese Folktales, Nagekeo - Pita, Yul Fulgensia Rusman; Pastika, I Wayan; Aryani, I Gusti Agung Istri (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2024)
This study explores the analysis of the cultural terms categorization and the degree of meaning equivalence through componential analysis. The data was taken from the Keonese folktales, entitled “Tonga Mbu’e So’a” (A Woman Called Tonga) and “Mbu’e Dombo Nio” (A Woman Called Dombo Nio: The Incarnation of Coconut Tree Becomes Human) written by Louise Baird and Philipus Tule, SVD. The source language of this research was Nagekeo Language Keo Dialect (NLKD) and the target language was English. Therefore, this research applied a qualitative method. In conducting this research, the techniques used were note-taking and observation. The data were displayed in the table, and the description was included along with the data. This study found 9 cultural terms categorization such as 6 ecology, 1 material culture, 1 social organisation, and 1 gesture and habits. Moreover, there are 6 fully equivalent, 1 partly equivalent with increased meaning, and 2 partly equivalent with decreased meaning. All the cultural terms are translated into equivalent meanings.